The early second-trimester multifetal pregnancy reduction improves pregnancy outcome - Jing-Jing Jiang; Ting Han; Yan-Hui Zhu (Clinical and Experimental Obstetrics & Gynecology)
Purpose: To evaluate pregnancy outcome of selective second-trimester multifetal pregnancy reduction (MFPR) compared with that of first-trimester MFPR, and control group which consists of women with ongoing primary twin pregnancies. Materials and Methods: This retrospective cohort study included all women with triplet pregnancies who underwent fetal reductions to twin pregnancies from January 2010 to December 2019 in Shandong Provincial Hospital. 154 MFPR were performed by intracardially injection of potassium chloride, 8 MFPR were performed by intracranially injection of potassium chloride. Reductions to monochorionic twins and reductions to one embryo were excluded. All procedures were performed at 12-24+6 wks gestation. The outcome of pregnancy in women with reduced triplets was compared with that of the control group. Results: We identified 162 women with reduced triplet pregnancies who underwent fetal reductions to twin pregnancies, and 160 women with ongoing primary twin pregnancies as the control group. There was a significant difference in the abortion rate between MFPR and control group. The abortion rate of the early second trimester MFPR group (at gestation 14-15+6 wks) (13.3%, 5/35) was not significantly different compared with that of the first trimester MFPR group (at gestation 12-13+6 wks) (8.3%, 8/96) or that of the control group (6.9%, 11/160). There were no significant differences in average gestation time at delivery, delivery rate in 28-34 wks, neonatal birth weight, gestational diabetes mellitus, or hypertensive disorder complicating pregnancy among the first trimester MFPR group , the early second trimester MFPR group, and the control group. Conclusion: In women with triplet pregnancy, fetal reduction in the early second trimester is an effective way to avoid delivery of abnormal fetuses, reduce complications during delivery, and improve neonatal quality.